The Effect of Financial Literacy on MSMEs Performance in Indonesian Non-Agricultural Production Firms - Ahmad Salim; Renny Friska (Jurnal Ilmiah Manajemen Kesatuan, 2026)
MSMEs play a vital role in driving local economic growth in emerging markets. However, many still struggle with performance issues, particularly due to weaknesses in financial management. This study aims to examine the effect of financial literacy on the performance of non-agricultural MSMEs in Demak Regency, Indonesia. A quantitative survey approach was employed, using structured questionnaires distributed to 120 MSME owners selected through purposive sampling. The data were analyzed using simple linear regression. The findings indicate that financial literacy has a positive and significant impact on MSME performance, reflected in increased revenue, improved cost efficiency, higher profitability, and enhanced business sustainability. Improved financial decision-making, effective cash flow management, and better access to formal financial services contribute to this performance improvement. This study contributes to the literature on MSMEs in developing countries by highlighting the link between financial literacy, financial inclusion, and local economic resilience. The results provide practical implications for local governments and development stakeholders in designing inclusive and sustainable MSME empowerment programs aligned with the Sustainable Development Goals.